(untitled) (Global Journal of Human-Social Science, 2023)
Although the field of Neurosciences has not had an exploration that is neither so recent nor so old particularly in the educational context there are still some spaces to be occupied by certain disciplines that integrated with them would lead to innovative and revolutionary solution strategies to the problems that demand a necessarily holistic response The objective of this paper is to make an assessment of the possibility of applying neuroscience to speech therapy as a pedagogical science based on a bibliographic review on the subject The result obtained favored the expansion of knowledge about the state of the art in which it was ventured and also made it possible to hypothesize about the improvement of the comprehensive speech therapy process for severe language disorders with the application of neurosciences